Exploring the role of encryption and the dark web in cyber terrorism: legal challenges and countermeasures in India - Hifajatali Sayyed; Sanu Rani Paul (Cogent Social Sciences)
The rapid growth of digital technologies has provided new opportunities for cyber criminals, including terrorist organizations, to exploit encrypted communications and the Dark Web for illicit activities. Cyber terrorism, characterized by the use of cyber-attacks to cause fear, disrupt societies, or damage national security, has become a significant threat in the modern world. Encryption technology ensures privacy and security for legitimate users, but it is also increasingly used by terrorists to coordinate attacks and evade detection. Simultaneously, the Dark Web offers anonymity, facilitating illegal activities such as recruitment, fundraising, and the planning of cyber-attacks. This research explores the intersection of encryption, the Dark Web, and cyber terrorism, examining the Indian legal implications of these technologies in facilitating terrorist activities. Using a doctrinal research methodology, this study analyzes existing Indian legal frameworks such as the Unlawful Activities (Prevention) Act and the Information Technology Act along with international conventions addressing encryption and the Dark Web. It evaluates the challenges posed by these technologies to law enforcement and the balance between national security and individual privacy rights. It evaluates potential countermeasures, including international cooperation, advanced decryption techniques, and policy reforms aimed at striking a balance between privacy and national security. This study provides insights into the growing threat posed by cyber terrorism in India and the urgent need for comprehensive legal and technological responses.